Implementasi Twitter Bootstrap dalam Pengembangan Aplikasi Web E-Commerce (Studi Kasus Toko Putra Reban Kendal) - Widayati, Yohana Tri; Prihati, Yani; Widjaja, Stephanus; Prakoso, Satrio Agung; Notobudojo, Angeline Renita (Jurnal Transformatika, 2021)
This study aims to apply twitter bootstrap in an e-commerce web so that the web display becomes more responsive, that is, it can provide a display according to the device used to access the web. The object of this research is the Putra Reban Store in Kendal which markets local art equipment and supplies, especially masks.The system development method used in this research is the Scrum method with stages including product backlog, sprint backlog, sprint and working increment. This method was chosen because it can save system development time and can transform a business that is difficult to measure into one that is easy to develop. The system is designed with 2 actors, namely admin and customer. Admin has access rights to manage product data, customer data, and order data, while customers have the right to access product data and make order transactions.With this developed system, it is easier for Putra Reban Stores to market their products because product descriptions and product availability stocks can be informed more easily and accurately. With complete and accurate product information, it will also be easier for customers to make transactions.